Osing Culture-Based Empowerment of the Millennials in Sapu Jagad Studio Banyuwangi Indonesia - Yulianingsih, Wiwin; Jacky, Muhammad; Nugroho, Rivo (International Journal of Psychosocial Rehabilitation, 2020)
Communities, particularly the millennials, are the main actors in development; thus, empowerment-based education is needed. A similar condition also applies for community groups whose survival depends on education. In order for the community to carry out its existential role, the young generation must continue to ingrain the community’s cultural values, knowledge, and skills. This study was aimed at describing the implementation of millennial empowerment based on Osing tribe culture in Sapu Jagad Sanggar, Kemiren Village, Banyuwangi. The research used participant observation method, in-depth interviews, and documentation of cultural activist millennials, village elders, and leaders in Sapu Jagad studio. The results of this study show that the millennial generation greatly values the traditional art of the Osing tribe and wishes to continue the preservation of their culture. This motivation is not only fostered by the nationalistic spirit but also by the philosophical values contained in every movement, dance, song, and ceremony that reflects the values of life.